Acute decrease in serum testosterone after a mixed glucose and protein beverage in obese peripubertal boys. (27th November 2014) - Schwartz, Alexander; Patel, Barkha P.; Vien, Shirley; McCrindle, Brian W.; Anderson, G. Harvey; Hamilton, Jill
Summary Background and objectives Delayed puberty and lower levels of testosterone (T) have been observed in adult obese males and some adolescent males. In adult men, enteral glucose ingestion results in acute lowering of serum testosterone levels; however, this has not been studied in adolescents. We aimed to examine the acute effect of a glucose/protein beverage on serum T concentration changes in obese peripubertal males. A second objective was to determine whether change in T concentration was related to appetite hormone levels. Patients and methods Twenty‐three overweight and obese males aged 8–17 in pre‐early (Tanner stage 1–2) and mid‐late (Tanner stage 3–5) puberty were included in this cross‐sectional study at the Clinical investigative unit at the Hospital for Sick Children. Participants consumed a beverage containing glucose and protein, and blood samples measuring pubertal hormones, ghrelin and glucagon‐like peptide‐1 (GLP‐1) were taken over 60 min. Results Across pubertal stages, there was a significant decrease in T levels in adolescent boys (−18·6 ± 3·1%, P < 0·01) with no proportional differences between pre‐early and mid‐late puberty (P = 0·09). Decrease in T was associated with a decrease in LH (r = 0·52, P = 0·02), and fasting T was inversely correlated with fasting ghrelin (r = −0·51, P = 0·03) with no correlation with GLP‐1. Conclusions Intake of a mixed glucose/protein beverage acutely decreases T levels in overweight and obese peripubertal boys. A potential mechanism for this decrease may be secondary to an acute decrease in LH, but this requires further evaluation.